Proses Filtrasi Sebagai Upaya Memperbaiki Kualitas Air Bersih Keluarga Balita Stunting - Supardi, Ardiani; Ardiani Septiati, Yosephina; Karmini, Mimin; Nurjaman, Ujang; Karjatin, Atin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Poor access to clean water can be an indirect cause of stunting in toddlers. This is because the need for clean water and sanitation at home is not met, this condition makes toddlers susceptible to diseases such as diarrhea. Activity objectives: increase community knowledge about how to process water, provide access to clean water for families of stunted toddlers, and improve water processing skills. Method: This activity is in partnership with Baleendah Community Health Center, RW 18 and RW 27, Baleendah sub-district. The method used is education and training on groundwater treatment with filtration, targeting 6 families of stunted toddlers and 30 community members. Results: There is an increase in knowledge and water quality. The water becomes colorless, odorless and clear and the levels of manganese and iron in clean water fall below the required levels. Conclusion: People understand and realize the importance of clean water, they can apply the filtration process to treat ground water. Families of stunted toddlers can have access to clean water by processing groundwater into clean water.